Making capitalism fit for society - Crouch, Colin 1944- (Polity Press, 2013)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies.